REVIEWING THE IMPLICATIONS OF TRAINING FOR ACADEMIC ADMINISTRATION STAFF AT CENTRAL MICHIGAN UNIVERSITY - Aljhany, Faddia Hmdan; Freed, David (Journal of Economics and Administrative Sciences, 2020)
Training has an effect on employees’ performances. Accordingly, the person who is responsible for employees’ development must figure out the most effective way to train and develop employees. Central Michigan University (CMU) has recognized the importance of providing appropriate training for employees who have a duty in advising students. The reason is that these employees have a significant impact on students’ educational performances. Thus, special attention to this category of employees is needed to improve advising quality. This research attempted to explore the impact of training on academic advising at CMU. Face-to-face interviews and online surveys were used as data collection tools for this study. The study scope consisted of professional and administrative employees who provide academic advising for students and two employees who provide academic advising for students in the MSA department. The primary question asked, what are the impacts of training on academic advisors at CMU? From the data collection, we found out that training had a major role in increasing the performance of professional and administrative employees when they served in an academic advising capacity. However, there were obstacles that the employees believed should be addressed, including unequal chances to receive training, inconsistent training, a focus on certain skills while others were ignored, a lack of trainers, problems in scheduling enough training time, lack of resources for maintaining policy awareness. Thus, this study provided recommendations to eliminate the negative outcomes of those obstacles. we suggested applying practices such as performing needs assessment for employees, evaluating training outcomes, presenting equal opportunities for receiving training, and providing available resources for employees to stay updated on the policy.